Literacy Education: helping EFL students achieve better learning outcomes - Syamsul Bahri; Iyehezkiel Parudani (Mitra Palupi, 2022)
Background: The development of technology has led to an increase in the interest of teenagers and students towards modern literary works so that literary works based on local wisdom are starting to be neglected. Purpose: This is the basis of this study developed to improve student literacy competence through the making of It-Based Bilingual Book of Folklore Drama Script which also aims to foster students’ interest in local culture. Design and methods: Classroom Action Research Method is used in this study. Results: The improving literacy competence experienced by students can be seen from the evaluation of the performance of the assignments they do. In Routine Task, students have an average score of 86.54. In Critical Journal Review task, the students' average has a literacy competence score of 87.90. In the Critical Book Review task, students have an average score of 89.33. Through the Mini Research task, the average score was 91.90. In the Idea Engineering tasks, the average score of students reached 90.27. In project assignments, it can be seen that the students' literacy competence increases in the aspects of reading, understanding and speaking with an average score of 94.09.